Teknik Listrik PERANCANGAN DAN PEMBUATAN MODUL BELAJAR RANGKAIAN MOTOR DAHLANDER 2 KECEPATAN BERBASIS PLC - Sugadul; syahrizal (ABEC Indonesia, 2021)
Dahlander motor is a 3-phase induction motor which has two speeds. The difference in speed on the Dahlander motor is obtained by the principle of changing the number of poles on the stator of the motor. By changing the number of poles on the Dahlander motor, it will change the speed of the motor. The purpose of this project development is to facilitate and help Caltex Riau Polytechnic students, especially students of the Electrical Engineering Study Program, this project was built using a Programmable Logic Controller or PLC so that the Dahlander motor control system can be done automatically. The PLC that will be used is the Schneider brand, type M221. To make PLC M221 program using Somachine Basic software. The working principle of this project is a dahlander motor control system, the control system is based on Supervisory Control And Data Acquisition (SCADA) using a PLC. The display of this control system is made using Wonderware InTouch software. With this project, it is hoped that it can help Caltex Riau Polytechnic students, especially for students of the Electrical Engineering Study Program. Keywords: Dahlander Motor, PLC Schneider M221, Somachine Basic, Wonderware InTouch, Electrical Engineering Study Program.